Relation of oncogenic microRNA-10b and microRNA-21 to glioblastoma size and localization - Nikitović Marina; Stepanović Aleksandar; Arsenijević Tatjana; Petrović Nina (Srpski Arhiv za Celokupno Lekarstvo)
Introduction/Objective. In glioblastoma, upregulation of oncogenic microRNA-10b (miR-10b) and microRNA-21 (miR-21) is often found. Our study aimed to investigate whether there is a link between miR-10b and miR-21 expression levels and tumor size and tumor localization. Methods. The research involved 43 patients diagnosed with glioblastoma. We analyzed the expression levels of miR-10b and miR-21 post-surgery. The data on tumor size and tumor localization were obtained from magnetic resonance imaging. Results The median expression level of miR-10b in patients with tumors < 4 cm was 214.86 (min–max: 2.13–816.89), while in patients with tumors ≥ 4 cm, the median expression level was 92.99 (min–max: 19.24–491.82). The median expression level of miR-21 in patients with tumors < 4 cm was 81.69 (min– max: 11.39–825.43), whereas in patients with tumors ≥ 4 cm, the median expression level was 40.84 (min–max: 2.68–278.98). For both miR-10b and miR-21, a statistically significant difference was found for tumors < 4 cm (p = 0.027 and p = 0.047, respectively) compared to those ≥ 4 cm. There was no statistically significant difference in the expression levels of miR-10b (p = 0.675) and miR-21 (p = 0.183) in relation to tumor localization. Conclusion. Glioblastomas smaller than 4 cm have statistically significantly higher expression levels of miR-10b and miR-21 compared to glioblastomas equal to or larger than 4 cm. Although this result is unexpected, it could mean that miR expression levels dynamically change after surgery and according to the altered microenvironment.